2020
DOI: 10.1002/mame.202000506
|View full text |Cite
|
Sign up to set email alerts
|

Facile Fabrication of Poly(vinyl alcohol)/Polyquaternium‐10 (PVA/PQ‐10) Anion Exchange Membrane with Semi‐Interpenetrating Network

Abstract: Anion exchange membranes (AEMs) are one of the core components of AEM fuel cells. A series of poly(vinyl alcohol)/polyquaternium‐10 (PVA/PQ‐10) AEMs with semi‐interpenetrating networks (s‐IPNs) are prepared by a simple solution‐casting method using glutaraldehyde (GA) as a cross‐linking agent. Subsequently, the prepared PVA/PQ‐10 cross‐linked membranes are characterized by Fourier transform infrared spectroscopy, scanning electron microscopy, thermogravimetric analysis, mechanical analysis, water uptake and sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 46 publications
1
17
0
1
Order By: Relevance
“…Active energy (Ea) is the minimum energy required for the chemical reaction. The lower the Ea, the lower the energy barrier for hydroxide transport [62,63]. The Ea values of QPPO-14, QPPO-13 and QPPO-7 are 12.26, 8.53 and 12.13 KJ mol -1 , respectively, lower than that reported for other AEMs (18 KJ mol -1 ) [64,65].…”
Section: A Comparison Of Membrane Properties Among Ion Exchange Membr...mentioning
confidence: 76%
“…Active energy (Ea) is the minimum energy required for the chemical reaction. The lower the Ea, the lower the energy barrier for hydroxide transport [62,63]. The Ea values of QPPO-14, QPPO-13 and QPPO-7 are 12.26, 8.53 and 12.13 KJ mol -1 , respectively, lower than that reported for other AEMs (18 KJ mol -1 ) [64,65].…”
Section: A Comparison Of Membrane Properties Among Ion Exchange Membr...mentioning
confidence: 76%
“…Ref. : KOH‐doped‐PVA; 116 PVA/CSPVA/CS ECNCM; 117 QCS‐PVA/QLDH@SiO 2 ; 118 PVA‐ b ‐PVBTAC; 59 QPVA/GO; 114 QPVA/GO; 119 PVA/PDDA/MWCNTs; 120 PVA/PDDA/nano‐zirconia; 121 QPVA/CS/MoS 2 ; 113 QPVA/nFS; 122 ; QCS‐PVA/LDH@CNTs; 123 QPPONF/PVA; 124 QPVA/Fe 3 O 4 @GO; 114 QPVA/GO; 125 PVA‐Silica/CNC; 126 PVA/PQ‐10; 127 Py‐PVA‐Silica; 21 and QPVBC/PVA IPN 115 . Abbreviations: CNC, cellulose nanocrystals; CSPVA, crosslinked sulfonated PVA; ECNFM, electrospun composite nanofiber membrane; FS, Fumed silica; IPN, interpenetrating polymer network; MWCNT, mutiwalled CNT; FCNT, functionalized CNT; MoS 2 , Molybdenum disulfide; PDDA, poly(diallyldimethylammonium chloride); PQ‐10, cationic hydroxyl ethyl cellulose (polyquaternium‐10); PVA‐ b ‐PVBTAC, poly(vinyl alcohol‐ b ‐vinyl benzene trimethyl ammonium chloride); QCS, quaternized chitosan; QLDH, quaternized layered double hydroxide; QPPONF, quaternized poly(2,6‐dimethyl‐1,4‐phenylene oxide) nanofiber; QPVA, quaternized PVA; QPVBC, quaternized poly(vinylbenzyl chloride)…”
Section: Pva‐based Membranes For Fuel Cellsmentioning
confidence: 99%
“…(b) Numerous studies have revealed that the construction of hydrophilic/hydrophobic microphase separation is another useful way to enhance the conductivity through the formation of “ion transport pathway.” 5,24 To achieve this favorite microstructure, block polymers, 25,26 graft polymers, 27 and polymers with local high‐density ionic groups 28 were synthesized, and a multistep synthetic routine is usually carried out. (c) Some functional fillers, including inorganic nanoparticles (eg, silica, 29 titanate nanotubes, 30 graphene sheets, 31 ) and organic components (eg, covalent organic frameworks 32 and poly(vinyl alcohol) 8 ), have been incorporated to fabricate composite or blend membranes with an enhanced conductivity. However, it is still a challenge to let the membranes simultaneously possess high‐conductivity and some other essential properties, such as high strength, low swelling, and eligible alkaline stability.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Generally, AEMs are casted from the polymer electrolytes, which are usually composed of a polymer skeleton, mobile anions and functional cationic groups. [6][7][8] So far, a variety of polymers, including aromatic polymers (eg, polysulfones, polyetherketones, polyphenylene ethers, polybenzimidazoles, etc.) [9][10][11][12] and aliphatic polymers (eg, polyvinyl alcohol, polyolefins, etc.…”
Section: Introductionmentioning
confidence: 99%